2010
DOI: 10.3109/13685531003657784
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of low bone mineral density in elderly males with chronic obstructive pulmonary disease: the role of body mass index

Abstract: OBJECTIVE: The aim of this study was to investigate the relationships between nutritional indices (Body mass index (BMI), serum albumin), sarcopenia, bone mineral density (BMD) and the severity of their pulmonary obstruction in elderly patients with chronic obstructive pulmonary disease (COPD). METHODS: The method involved was a prospective transversal study; 82 males >65 years old, 41 stable patients with COPD and 41 healthy elderly individuals (controls). All subjects underwent spirometry, biochemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…As mentioned above, osteoporosis and sarcopenia have common causal factors such as low levels of vitamin D, testosterone, estrogen, and insulin, as well as, reduced calorie intake and malnutrition (9, 10, 11). The present study identified that sarcopenia can increase the risk of osteoporosis and may lead to increased risk of bone fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, osteoporosis and sarcopenia have common causal factors such as low levels of vitamin D, testosterone, estrogen, and insulin, as well as, reduced calorie intake and malnutrition (9, 10, 11). The present study identified that sarcopenia can increase the risk of osteoporosis and may lead to increased risk of bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, sarcopenia is defined as a systemic continuous decrease in skeletal muscle strength and muscle mass so that the diagnosis of sarcopenia must be supported by decreased muscle mass and functional muscle strength (8). Until now, many studies of muscle mass and BMD have been carried out (9, 10, 11), and they showed that low muscle mass is correlated with low BMD. Unfortunately, their study populations were inconsistent and their definitions of sarcopenia different.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported significant correlation between sarcopenia and osteoporosis and/or BMD. Coin et al124 detected a significant higher prevalence of osteoporosis in sarcopenic groups compared with non-sarcopenic groups (46% vs. 0%; P <0.05). Bolton et al similarly reported a very high prevalence of osteoporosis (50%) and osteopenia (50%) in cachectic COPD patients 125.…”
Section: Risk Factors For Osteoporosis In Copdmentioning
confidence: 95%
“…Thus the prevalence of osteoporosis is higher in patients with COPD and low body mass index [174] and the same is true of sarcopenia, the main cause of weight loss in COPD, suggesting a common factor for these two extrapulmonary manifestations of COPD [175].…”
Section: Doi: 101183/0903193600134014mentioning
confidence: 96%